Pendidikan Keagamaan Pada Komunitas Anak Jalanan Kota Banjarmasin - Tarwilah, Tarwilah (IAIN Antasari Banjarmasin, 2013)
The presence of homeless children has been commonly visible in big cities in Indonesia. Children are a gift and trust of God that in them inherent dignity as human must be respected. Childrenâs rights are part of human rights as contained in the 1945 Constitution, Law No. 39, 1999 on Human Rights, The President Decree of The Republic of Indonesia No. 36, 1990 on the ratification of Convention on the Rights of the Child. The phenomenon of homeless children in Indonesia, especially in big cities such as Banjarmasin, is increasingly complex. This writing is to find out how the religious education takes part in the homeless childrenâs everyday life in Banjarmasin.